The maintenance of modified electroconvulsive therapy combined with risperidone is better than risperidone alone in preventing relapse of schizophrenia and improving cognitive function - Ying Yang; Xiaojing Cheng; Qingzhi Xu; Renjun Li; Zengxun Liu; Liping Wang; Yanqing Zhang; Guoqiang Ren; Jintong Liu (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To evaluate the effect of maintenance modified electroconvulsive therapy (MECT) on schizophrenic patients. Methods From June 2012 to June 2014, 62 patients with schizophrenia, who had recovered from a successful course of acute MECT, were recruited. Thirty-one patients received maintenance MECT and risperidone, as the experimental group. Another 31 patients were enrolled in the control group, and received risperidone only. The effects on cognitive functions, clinical symptoms and relapse rate were determined. Results Patients in the experimental group had a lower relapse rate and longer relapse-free survival time than the controls. Relative to the baseline evaluation, patients showed statistically significant improvement in verbal memory and visual memory. At the final assessment, the scores of verbal and visual memory were remarkably lower in the experimental group than the controls but there was no significant difference in other tests. Conclusion Maintenance MECT plus medication is superior to medication alone in preventing relapse and improving cognitive function.